A threefold examination of university digital leadership, teacher digital competency, and teacher technology behavior for digital transformation of education - Zhu, Rui; Bity Salwana, Alias; Mohd Izham, Mohd Hamzah; Mohd Rashid, Ab Hamid (Society for Research and Knowledge Management, 2024)
In the digital age, it is imperative that Higher Education Institutions (HEIs) should cultivate digital talent to adapt to social development and occupational requirements. To achieve this, HEIs need to effectively implement digital transformation by understanding how leadership and teacher competencies contribute to technology use in educational settings. This study explored universities’ digital leadership and its relationship with teacher technology behavior, with teacher digital competency serving as a mediating variable in universities from Jilin Province, China. Data were collected through convenience sampling of 402 teachers from 25 universities in Jilin Province, and analyzed using descriptive analysis and structural equation modeling. Findings revealed that all three key variables are highly significant. Moreover, digital leadership has a strong effect on teacher digital competency, a weak effect on teacher technology behavior, and teacher digital competency has a moderate effect on teacher technology behavior. The findings also indicated that teacher digital competency mediates the relationship between digital leadership and teacher technology behavior. In conclusion, this study provides valuable insights into the ways in which HEIs can navigate digital transformation by leveraging leadership and focusing on building teacher competency, which in turn can enhance technology usage in teaching practices. This study considered how higher education institutions can cope with the complex challenges of the digital age and suggested ways in which the implications of this research can better enable universities to promote digital transformation. © Authors This work is licensed under a Creative Commons Attribution-NonCommercial-NoDerivatives 4.0.